2016
DOI: 10.1016/j.neulet.2016.04.027
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG-PET imaging of rat spinal cord demonstrates altered glucose uptake acutely after contusion injury

Abstract: Spinal cord injury (SCI) results in an acute reduction in neuronal and glial cell viability, disruption in axonal tract integrity, and prolonged increases in glial activity and inflammation, all of which can influence regional metabolism and glucose utilization. To date, the understanding of glucose uptake and utilization in the injured spinal cord is limited. Positron emission tomography (PET)-based measurements of glucose uptake may therefore serve as a novel bio-marker for SCI. This study aimed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
(32 reference statements)
0
25
0
Order By: Relevance
“…These changes were observed in both white and gray matter at the lesion site (Schechter et al, 1990). In a rat model of moderate contusion SCI, we have found that injury resulted in a marked reduction in glucose uptake at 6 h post-injury, as measured by FDG-PET imaging (von Leden et al, 2016). This glucose uptake depression then returned to baseline levels and remained there throughout the following 2 weeks of the study, although other studies have suggested that the uptake of FDG increases after the first 24 h, to peak at 7 days post-injury (Nandoe Tewarie et al, 2010).…”
Section: No Hypoglycemiamentioning
confidence: 80%
See 1 more Smart Citation
“…These changes were observed in both white and gray matter at the lesion site (Schechter et al, 1990). In a rat model of moderate contusion SCI, we have found that injury resulted in a marked reduction in glucose uptake at 6 h post-injury, as measured by FDG-PET imaging (von Leden et al, 2016). This glucose uptake depression then returned to baseline levels and remained there throughout the following 2 weeks of the study, although other studies have suggested that the uptake of FDG increases after the first 24 h, to peak at 7 days post-injury (Nandoe Tewarie et al, 2010).…”
Section: No Hypoglycemiamentioning
confidence: 80%
“…In addition, we demonstrated that these changes in glucose uptake were dependent on subject age. Increasing the age of rats from 3 months (von Leden et al, 2016) to 12 months (von Leden et al, 2019) resulted in a significant alteration in the glucose uptake profile. Aged rats showed no significant change in glucose uptake acutely after injury, but did show a marked increase in glucose uptake by 14 days post-injury (von Leden et al, 2019).…”
Section: No Hypoglycemiamentioning
confidence: 99%
“…Studies have shown that energy fluctuations caused by changes in glucose uptake are closely linked to the survival of the neurons [ 5 , 9 ]. After SCI, the glucose uptake of the spinal cord of rodents was decreased, with the metabolism disturbance, and neuronal activity was inhibited [ 32 ]. The entry of glucose into cells depends on glucose transporters.…”
Section: Discussionmentioning
confidence: 99%
“…In order to normalize the primary SUV to the relative SUV (SUVR), the cerebellum and baseline in its resting state after SCI for a week were used as the reference (31,32). The SUVR was expressed as the average of three SUVRs by repeating the measurement three times.…”
Section: Pet-ct Quality Controlmentioning
confidence: 99%
“…The main mechanism underlying this phenomenon is that electrical stimulation induces vasodilation via the release of vasoactive neuropeptides such as calcitonin gene-related peptide and pituitary adenylate cyclase-activating polypeptide in the dura mater, increasing blood supply to the stimulated area (50,51). Nevertheless, it is not clear why WEES alone cannot increase task metabolism compared with its matched basal metabolism; however, this is likely because hemodynamic response and glucose uptake involve different processes (16,31,52). While WEES alone increased the blood supply, the WEES-induced locomotor intensity was relatively low and could not therefore fully stimulate the spinal cord neural cells to uptake proportionally matched glucose.…”
Section: Discordance Between Hemodynamic Response and Glucose Uptakementioning
confidence: 99%